2018
DOI: 10.1111/1442-1984.12208
|View full text |Cite
|
Sign up to set email alerts
|

Seed storage of Brazilian cacti species in different threat categories

Abstract: Cactaceae is considered the fifth most endangered taxonomic group. In light of this, the aim of this study was to evaluate the efficiency of different low‐temperature storage techniques in maintaining the viability of seeds of cacti in different threat categories. Seeds of six cacti taxa were stored in a cold chamber (8°C), a freezer (−5°C), in liquid nitrogen (−196°C) and at room temperature (25–27°C) for a period of 0, 1, 3, 6, 9 and 13 months. At each evaluation interval we removed a seed sample for each ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…For the seeds from the Atlantic Forest area (Figure 3D), there was no significance in the data for the packages, which remained high for all periods. This germinal response can be explained by the reduction in seed metabolism and the degradation of storage compounds at lower temperatures (Santos et al, 2018). These results demonstrate that the refrigerator provided an adequate condition for the conservation of the seeds of this species when compared to room temperature, providing similar germination percentages over the twelve months of storage, regardless of the packaging.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…For the seeds from the Atlantic Forest area (Figure 3D), there was no significance in the data for the packages, which remained high for all periods. This germinal response can be explained by the reduction in seed metabolism and the degradation of storage compounds at lower temperatures (Santos et al, 2018). These results demonstrate that the refrigerator provided an adequate condition for the conservation of the seeds of this species when compared to room temperature, providing similar germination percentages over the twelve months of storage, regardless of the packaging.…”
Section: Resultsmentioning
confidence: 70%
“…Seed storage is a conservation method that aims to preserve the physical and physiological quality of seeds, allowing them to remain viable for long periods and to be used for various purposes, such as studies on genetic, morphological and physiological diversity of the species, formation of germplasm banks and reforestation (Silva et al, 2011). Research related to the conservation, longevity and viability of seeds of cactaceous plants endemic to Brazil are still lacking studies and few data are found in the literature, as exemplified by the works reported by Abud et al (2012), Abud et al (2016), Nascimento & Meiado (2016), Santos et al (2018) and Silva et al (2018). However, although papers on the conservation of Cereus jamacaru seeds have been found, they did not involve seeds from different ecosystems and did not evaluate the behavior of the seeds regarding storage for long periods.…”
Section: Introductionmentioning
confidence: 99%
“…Although in the present review the seed desiccation tolerance and the longevity of cactus seeds have been commented on, few studies have evaluated the seed preservation in controlled conditions. Only in 20 species has a preservation at -0 °C been evaluated, up to a maximum of 13 months (Nolasco et al 1996, Veiga-Barbosa et al 2010, Goodman et al 2012, Marchi et al 2013, Salazar et al 2013, Bárbara et al 2015, Civatti et al 2015, Dos Santos et al 2018. Studies of this type are necessary when faced with the increasing threats that confront the family (Goettsch et al 2015) and the need to search for secure alternatives for long-term preservation.…”
Section: Seed Storage At Low Temperaturesmentioning
confidence: 99%
“…Furthermore, it is important to create complementary initiatives, such as ex situ conservation (MMA 1992), considering their viability and simplicity to maintain a species (Cohen et al 1991). Some studies have already been carried out for endangered species of cacti examining conservation initiatives such as micropropagation in vitro (Marchi 2016;Palacios et al 2016;Civatti et al 2017a;Torres-Silva et al 2018), living collections (Hultine et al 2016;Cavalcante et al 2017) and seed storage (Civatti et al 2015;Nascimento & Meiado 2016;Santos et al 2018); these works are crucial to facilitate future studies and to protect the species from extinction.…”
Section: Conservation Of D Zehntneri Subsp Petr-halfarimentioning
confidence: 99%